Implantación del sistema de costos por órdenes de producción en maderas del sur de la ciudad de Loja, período del 01 de enero al 31 de marzo del 2014 - Mingo Morocho, María Fernanda (2016)
he implementation of this research regarding "IMPLEMENTATION OF SYSTEM FOR ORDERS PRODUCTION IN THE SOUTH COST WOODS CITY LOJA, FOR THE PERIOD FROM 01 JANUARY TO 31 MARCH 2014.", Was held in based on the need to provide a system that optimizes and run efficiently control the economic, financial and production activities of the company, which will contribute to the effective development of it. The objectives of this research were fulfilled to apply the accounting process for Production Orders in the company. First a proper accounting of the cost elements was developed, and then determine the unit and total cost of goods manufactured in a period of three months, to thereby establish or sale price and a reasonable profit, another objective principal was to present the financial statements as: Cost of Goods Sold, Income Statement, Statement of Financial Position and Cash Flows, the same who provided timely and reliable financial information. Finally it is concluded that the application of cost system costs and expenses arising in the manufacture of finished furniture, just as with the design and use of accounting records control and distribution of materials is facilitated established, labor and manufacturing overhead costs. Financial statements in the current economic state of the company and its obligations were developed acquired is reflected. Thus with the background indicated the owner suggested the ongoing implementation of an accounting system Cost Of Production Orders, and thus have an effective tool that allows you to get efficient accounting information for decision making.